Is periodontitis a potential risk factor of rhegmatogenous retinal detachment? A population-based retrospective cohort study of Taiwan - Earl Fu; Yueh-Ju Tsai; Chi-Hsiang Chung; Min-Wen Fu; Yi-Jan Hsia; Wu-Chien Chien (Journal of Dental Sciences, 2025)
Background/Purpose: Periodontitis, a common inflammatory disease, has been linked to various systemic and ocular conditions. However, its connection to rhegmatogenous retinal detachment (RRD), a vision-threatening condition, remains uncertain. This study aimed to investigate the association between periodontitis and RRD. Materials and methods: From 2000 to 2015, 1,936,512 participants were recruited from Taiwan's National Health Insurance Research Database, including 29,970 with chronic periodontitis, defined by at least three outpatient visits within a year. A matched 1:1 comparison group was selected based on sex, age, and index year. The periodontitis group was divided into two subgroups: those who received root planing and/or surgical therapy (subgroup 1) and those who did not (subgroup 2). Results: At the end of the follow-up, 2165 participants in the periodontitis group and 1259 in the comparison group developed RRD. The cumulative risk of RRD was increased in the periodontitis group, and the two subgroups, compared to the comparison group. After adjustment with the covariates of sociodemographic factors, systemic diseases, RRD comorbidities, and smoking/alcohol habits, the increased risk of developing RRD remained significant (adjusted hazard ratio: 1.49, 95 % CI: 1.12–1.83, P < 0.001). Subgroups 1 and 2 also had increased risks, with adjusted hazard ratios of 1.70 and 1.34, respectively. These results persisted even when excluding the first 1 or 5 years of data. Conclusion: This nationwide retrospective study showed that patients with chronic periodontitis, regardless of whether they received periodontal treatment, had a higher risk of developing RRD, suggesting a potential association between periodontitis and RRD.